ANALISIS PENGARUH PINJAMAN TERHADAP SISA HASIL USAHA PADA KOPERASI CU BETANG ASIPALANGKA RAYA DI ERA DIGITAL 5.0 - Pamungkur Pamungkur; Sunarmie Sunarmie (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aimed to know the loan at Koperasi Pegawai Pemerintah Bandung, to know the net profit at Koperasi CU Betang Asi Palangka Raya, and to know the influence of loan to the net profit at Koperasi CU Betang Asi Palangka Raya. The method of this research used descriptive with a quantitative approach that mean the results were then processed and analyzed for to be concluded. From the research result by using hypothesis testing correlation coefficient analysis there was a relationship between loan and net profit which was positive and very strong with its value of 0,943. The value of coefficient determination R Square was 0,889 or 88,9% indicating there was an influence as much as 88,9% and 11,1% by other factors which were not observed in this research. The result of test T was T count > T table = 6,330> 2,365. So it could be concluded that the loan had a positive influence and signifikan impact to net profit. There were the following research problems: (1).The new members who borrowed large amounts of money, (2). Mutations of employee to out of town who still had loans to cooperative, and (3). Members who still had loans but had to retire. And suggestions to resolve the problem are as follows: (1).To provide a guarantee, (2).To coordinate with the members in amicably, and (3). Principal members are converted to loans remaining.